(untitled) (Journal of Engineering, 2015)
In this paper, effective slab width for the composite beams is investigated with special emphasis on the effect of web openings. A three dimensional finite element analysis, by using finite element code ANSYS, is employed to investigate shear lag phenomenon and the resulting effective slab width adopted in the classical T-beam approach. According to case studies and comparison with limitations and rules stipulated by different standards and codes of practice it is found that web openings presence and panel proportion are the most critical factors affecting effective slab width, whereas concrete slab thickness and steel beam depth are less significant. The presence of web opening reduces effective slab width by about 21%. Concentrated load produces smaller effective slab width when compared with uniformly distributed and line loads. Generally, standard codes of practice overestimate effective slab width for concentrated load effect, while underestimate effective slab width for uniformly distributed and line load effect. Based on the data available, sets of empirical equations are developed to estimate the effective slab width in the composite beams with web openings to be used in the classical T-beam approach taking into account the key parameters investigated.